PENGARUH PENGAJIAN RUTIN TERHADAP SPIRITUAL QUOTIENT IBU-IBU MAJELIS TAKLIM AL AMIN - Yasmine Acilia Az-zahra; Bambang Haryanto (Yonetim Jurnal, 2024)
The aim of this research was to determine the effect of routine recitation on the spiritual quotient of the women of the Bukit Baru Palembang Ta'lim Council. This research uses quantitative methods, with the independent (X) influence of routine recitation and the dependent variable (y) Spiritual Quotient. With a population of 35 members of the permanent member congregation, while the sample was 32 members of the Al Amin Ta'lim Majlis, the research used the SPSS version 26 program. The results of the study showed that the calculated t value was 1.836 while the t table value was 1.697 or t value. count > table t value. So Ho is accepted and it is concluded that recitation has an effect on the spiritual quotient.